1998
DOI: 10.1073/pnas.95.12.6983
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of transforming growth factor β1 in arterial endothelium causes hyperplasia, apoptosis, and cartilaginous metaplasia

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
129
2
3

Year Published

2000
2000
2013
2013

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 173 publications
(138 citation statements)
references
References 40 publications
(46 reference statements)
4
129
2
3
Order By: Relevance
“…In the heart, Sox9 is required for proper organization the valvular ECM proteins (60), whereas in the gonads, Sox9 regulates many ECM proteins as well as modifiers of the ECM such as matrix metalloproteinases (61,62). Sox9 also plays a role in fibrotic and sclerotic disorders in various tissues, in which Sox9 causes excessive and inappropriate ECM deposition by activating ECM proteins (63)(64)(65)(66)(67)(68). Furthermore, Sox9 plays a critical role during chondrogenesis (30), and ChiP analysis in chondrocytes has shown that Sox9 directly binds to loci of 18 different ECM genes, including Col2a1 (69).…”
Section: Discussionmentioning
confidence: 99%
“…In the heart, Sox9 is required for proper organization the valvular ECM proteins (60), whereas in the gonads, Sox9 regulates many ECM proteins as well as modifiers of the ECM such as matrix metalloproteinases (61,62). Sox9 also plays a role in fibrotic and sclerotic disorders in various tissues, in which Sox9 causes excessive and inappropriate ECM deposition by activating ECM proteins (63)(64)(65)(66)(67)(68). Furthermore, Sox9 plays a critical role during chondrogenesis (30), and ChiP analysis in chondrocytes has shown that Sox9 directly binds to loci of 18 different ECM genes, including Col2a1 (69).…”
Section: Discussionmentioning
confidence: 99%
“…In this context, it is worth noting that direct transfer of TGF-␤ 1 gene into arteries results in fibrocellular hyperplasia (33) and that this multifunctional cytokine also can induce vascular smooth muscle cell hypertrophy (34). Transdifferentiation of vascular smooth muscle cells into chondrocytes and intimal growth also have been observed after transfection of the TGF-␤ 1 gene into murine arteries (35). Differential sensitivity of vascular cells to TGF-␤ 1 signaling also might be relevant because TGF-␤ 1 is reported to potentiate platelet-derived growth factor (PDGF)-induced proliferation of vascular smooth muscle cells of the spontaneously hypertensive rat but not the vascular smooth muscle cells of the normotensive Wistar-Kyoto rat (36).…”
Section: How Might Tgf-␤1 Contribute To the Pathogenesis Of Hypertensmentioning
confidence: 99%
“…TGF-b signaling affects both vascular differentiation and proliferation, and overexpression of the TGF-b1 ligand promotes intimal growth and apoptosis simultaneously in vascular endothelium. 32 The pleiotropic nature of TGF-b as a growth factor offers a potential explanation for the variable complications of hereditary hemorrhagic telangiectasia. The net effect of dysfunction of activin-receptor-like kinase 1 may depend on local vascular interactions and other environmental or genetic factors.…”
Section: Known Features Of Phmentioning
confidence: 99%